Analisa Produksi Batubara Sebagai Bagian Dari Supply Chain - Kurniaty Ratoko, Sita; Yazid Bustommy, Abby; Sugiarto, Emaria (JOURNAL INFORMATION TECHNOLOGY ENGINEERING AND SCIENCE, 2022)
PT Servo Buana Resources as one of the largest and leading coal mining companies in Indonesia, SBR has good quality coal to offer to consumers who need high quality coal fuel for industrial needs, thus being able to meet market needs for coal fuel. Innovative and quality products, companies need to carry out Coal Production Analysis as Part of the Supply chain so that consumer demand can be met. By minimizing idle time for machines and workers and using maximum resources so that high productivity is obtained. Practical Work is carried out at PT Servo Buana Resources in the coal production section. The purpose of this practical work is to analyze Coal Production as Part of the Supply chain used by PT SBR and analyze the results of the Supply chain used by the company. In the process of planning and controlling production, there is a process that is important in maximizing the efficiency of every resource that exists in a production system, namely the process of maximizing where production is based on consumer demand and the capacity of the resources owned.